Pengaruh Motivasi, Persepsi dan Sikap Terhadap Keputusan menjadi Agen Asuransi Syariah - Maisyaroh, Elvira; Anggraini, Tuti; Inayah, Nurul (Universitas Islam Negeri Sumatera Utara, 2023)
This study aims to analyze the influence of motivation, perception and attitude variables on the decision of UIN Sumatera Utara insurance students to become sharia insurance agents. This study uses a quantitative research method. Data collection was carried out by distributing questionnaires to respondents. The population in this study was 450 UIN Sumatera Utara sharia insurance students. Samel in this study used a random sampling approach, a sample of 212 respondents was taken and then measured using a Likert scale. The data processing process used SPSS 26. The results showed that the motivation variable had a positive and significant effect on students' decisions to become insurance agents. The perception variable had a positive and significant effect on students' decisions to become insurance agents. The attitude variable did not have a positive and significant effect on students' decisions to become insurance agents. Simultaneously, the Motivation variables (X1), Perception (X2), and Attitude (X3) together influenced the decision to become sharia insurance agents. So with motivation, perception, and attitude, students can have a decision to become insurance agents